Organic Biogeochemistry in West Mata, NE Lau Hydrothermal Vent Fields. (21st April 2021) - Lin, H.‐T.; Butterfield, D. A.; Baker, E. T.; Resing, J. A.; Huber, J. A.; Cowen, J. P.
Abstract: The impact of submarine hydrothermal systems on organic carbon in the ocean—one of the largest fixed carbon reservoirs on Earth—could be profound. Yet, different vent sites show diverse fluid chemical compositions and the subsequent biological responses. Observations from various vent sites are to evaluate hydrothermal systems' impact on the ocean carbon cycle. A response cruise in May 2009 to an on‐going submarine eruption at West Mata Volcano, northeast Lau Basin, provided an opportunity to quantify the organic matter production in a back‐arc spreading hydrothermal system. Hydrothermal vent fluids contained elevated dissolved organic carbon, particulate organic carbon (POC), and particulate nitrogen (PN) relative to background seawater. The δ 13 C‐POC values for suspended particles in the diffuse vent fluids (−15.5‰ and −12.3‰) are distinct from those in background seawater (−23 ± 1‰), indicative of unique carbon synthesis pathways of the vent microbes from the seawater counterparts. The first dissolved organic nitrogen concentrations reported for diffuse vents were similar to or higher than those for background seawater. Enhanced nitrogen fixation and denitrification removed 37%–89% of the total dissolved nitrogen in the recharging background seawater in the hydrothermal vent flow paths. The hydrothermal plume samples were enriched in POC and PN, indicating enhanced biological production. The total "dark" organic carbon production within the plume matches the thermodynamic prediction based on available reducing chemical substances supplied to the plume. This research combines the measured organic carbon contents with thermodynamic modeled results and demonstrates the importance of hydrothermal activities on the water column carbon production in the deep ocean. Plain Language Summary: External energies fuel the production of organic carbon and nitrogen by living organisms. Exploring the organic compounds' concentrations and characteristics help reveal the energy flow and biogeochemical processes. Here, we investigate the marine organic matter in the submarine hot springs (hydrothermal fluids) generated by deep seawater interacting with uplifting magma caused by spreading seafloor. We surveyed the organic carbon and nitrogen contents with samples collected during a cruise in May 2009, in response to an on‐going submarine eruption at West Mata Volcano, northeast Lau Basin. The submarine hot spring water, relative to background seawater, had elevated organic carbon and nitrogen with unique characters. The amount of elevated organic carbon meets our calculated values based on the energy that the hot spring brings to marine life. We conclude that the underwater hot springs fuel "dark" organic carbon production via unique carbon fixation pathways in the deep ocean. Key Points: Unique stable carbon isotope of suspended particulate organic carbon is indicative of unique carbon fixation pathway by vent biomes We estimated first dissolved organic nitrogen for hydrothermal vent fluids and observed enhanced nitrogen fixation and/or denitrification Total dark organic carbon production within the plume matches thermodynamic prediction based on available, reducing chemical substances